Winemaking with vine-shoots. Modulating the composition of wines by using their own resources - Cebrián-Taracón, Cristina (2019)
Vine-shoots from two important Vitis vinifera, Airén and Cencibel, have been prepared in two different formats (chip and granule) and added (12 g/L) in their own wines in different winemaking steps. Results have shown significant differences depending in all conditions tested, and wine chemical composition was modulated while in contact with vine-shoots. Compounds such as trans-resveratrol, increased its concentration up to 4 mg/L in Airén white wines. In Cencibel red wines, vanillin was found in a concentration four times above its odor threshold and independently of the vine-shoot variety, format and moment of addition, compounds such as (−)-epicatechin and (+)-catechin increased the concentration with respect to the control wine. When vineshoots were added after fermentation, β-ionol appeared for first time in all wines. In case of guaiacol, the higher increment was observed for Airén wines. Therefore, it is possible to elaborate distinctive wines using their own resources.